2009
DOI: 10.1111/j.1600-0587.2008.05694.x
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐sensitive landscape complementation determines habitat suitability for a territorial generalist

Abstract: Evaluating habitat suitability is often complex, as habitat effects may be scale-dependent, critical resources may be spatially segregated, and resource availability may also depend on intra-and inter-specific interactions. Using analyses that spanned multiple years and spatial scales, we investigated habitat requirements of a territorial generalist, the common raven Corvus corax, in a relatively pristine woodland, Bial owieża Forest (E Poland). We compiled data from multiple raven surveys conducted between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…We demonstrated that the nested microhabitat and plot-scale variables both appear to significantly influence habitat quality for reef-associated fishes, but the effects varied among components of the fish community and plotscale coral density was only correlated with the abundance of adult fishes. The importance of assessing habitat quality at multiple scales has been recognised in a variety of ecosystems including woodland birds (Mueller et al 2009 Despite the growing recognition of the importance of both abiotic and biotic controls of habitat quality, an analysis of 173 ornithological studies demonstrated that only 6% considered how constraints such as predation or competition affected habitat quality (Johnson 2007). Our study adds to the literature on abiotic and biotic controls of habitat quality in reef fishes by demonstrating how both the competitive effects of territorial damselfishes and abiotic habitat quality are correlated with the abundance of reef-associated species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We demonstrated that the nested microhabitat and plot-scale variables both appear to significantly influence habitat quality for reef-associated fishes, but the effects varied among components of the fish community and plotscale coral density was only correlated with the abundance of adult fishes. The importance of assessing habitat quality at multiple scales has been recognised in a variety of ecosystems including woodland birds (Mueller et al 2009 Despite the growing recognition of the importance of both abiotic and biotic controls of habitat quality, an analysis of 173 ornithological studies demonstrated that only 6% considered how constraints such as predation or competition affected habitat quality (Johnson 2007). Our study adds to the literature on abiotic and biotic controls of habitat quality in reef fishes by demonstrating how both the competitive effects of territorial damselfishes and abiotic habitat quality are correlated with the abundance of reef-associated species.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating how individuals of a species respond to varying habitat quality is complex because of scale-dependent responses and the combined influence of biotic and abiotic factors (Mueller et al 2009). This study supports the growing recognition that both biotic variables and scale-dependent effects must be considered when assessing habitat quality, which traditionally assesses only abiotic variables and is measured at a single scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of two habitat generalist and specialist plants showed the habitat generalist species could not be successfully modelled because of inconsistent results for variables when using different model methods and overall low model performance when compared with the specialists' model performance (Evangelista et al, 2008). In contrast, Mueller et al (2009) found that generalist crows could be successfully modelled when different habitat designations and spatial scales were considered. Grey wolves are a wide-ranging habitat generalist with the potential to have conflicts with humans and livestock.…”
Section: Discussionmentioning
confidence: 96%